LEGAL AWARENESS AND LEGAL CULTURE: INTERNATIONAL EXPERIENCE AND NATIONAL APPROACHES - Mohidil Bozorova (Modern American Journals, 2025)
This article examines the theoretical foundations of legal awareness and legal culture, their significance in social development, and the processes of their formation based on international experience. The aim of the study is to explore international practices in developing legal culture and to identify possibilities for implementing such experiences in Uzbekistan.
Keywords: Legal awareness, legal culture, international experience, legal reforms, legal education, civil society.